Orphanhood and Human Capital Destruction: Is There Persistence into Adulthood? - Beegle, Kathleen; De Weerdt, Joachim; Dercon, Stefan (2012)
This article presents unique evidence that orphanhood matters in the long run for health and education outcomes in a region of northwestern Tanzania. We study a sample of 718 non-orphaned children surveyed in 1991-1994 who were traced and reinterviewed as adults in 2004. A large proportion, 19%, lost one or more parents before age 15 in this period, allowing us to assess permanent health and education impacts of orphanhood. In the analysis, we control for a wide range of child and adult characteristics before orphanhood, as well as community fixed effects. We find that maternal orphanhood has a permanent adverse impact of 2 cm of final height attainment and one year of educational attainment. Expressing welfare in terms of consumption expenditure, the result is a gap of 8.5% compared with similar children whose mothers survived until at least their 15th birthday.